2017
DOI: 10.1080/10410236.2017.1289437
|View full text |Cite
|
Sign up to set email alerts
|

The Exchange of Social Support on Online Bariatric Surgery Discussion Forums: A Mixed-Methods Content Analysis

Abstract: Bariatric surgery patients often experience physical and psychosocial stressors, and difficulty adjusting to significant lifestyle changes. As a result, social support groups that provide patients with support, coping skills, and nutritional information are valuable components of bariatric care. Support group attendance at bariatric centers is associated with greater post-surgery weight loss; however, several barriers hinder attendance at in-person support groups (e.g., travel distance to bariatric centers). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 22 publications
1
53
1
1
Order By: Relevance
“…Only two studies included a theoretical/conceptual framework, Discursive Psychology 34 and the Social Support Behavioral Code Model. 35 Reviews A total of six reviews were found in the literature search that discussed various eHealth strategies targeting MBS patients including telemedicine, web-based media, smartphone apps and wearables to track activity levels. In general, most reviews concluded that eHealth strategies can assist patients undergoing MBS in both pre-and post-operative acquisition of health information and knowledge as well as personal feedback to assist them with weight loss and improved lifestyle habits.…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies included a theoretical/conceptual framework, Discursive Psychology 34 and the Social Support Behavioral Code Model. 35 Reviews A total of six reviews were found in the literature search that discussed various eHealth strategies targeting MBS patients including telemedicine, web-based media, smartphone apps and wearables to track activity levels. In general, most reviews concluded that eHealth strategies can assist patients undergoing MBS in both pre-and post-operative acquisition of health information and knowledge as well as personal feedback to assist them with weight loss and improved lifestyle habits.…”
Section: Resultsmentioning
confidence: 99%
“…The codes were established based on the categories of Xu and Burleson's (2001) typology. This method allows researchers to analyze manifest and latent meaning of communication, and to systematically code and categorize data using a validated theoretical framework (Atwood, Friedman, Meisner, & Cassin, 2018). The sentence in each blog post served as the unit of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Koball et al, on the contents of Facebook support groups, was performed using a quantitative approach, meaning that the most common topics of conversation could be identified by frequency and proportion, but not analysed in any deeper or qualitative manner [ 27 ]. A study by Atwood et al used the Social Support Behavior Code to categorise posts on a bariatric support group discussion forum, and found that informational and emotional support posts were the most common categories [ 44 ]. Both of these previous studies were conducted using material from the US, meaning that the results are influenced by the specific political and healthcare policy-related circumstances of that country.…”
Section: Discussionmentioning
confidence: 99%